Memory matters : contexts for understanding sexual abuse recollections - Haaken, Jan; Reavey, Paula (Routledge, 2010)
In this volume, the editors make use of current memory scholarship to explore ethical, moral and cultural issues that continue to shape the ways in which memory is conceived in a range of scientific, therapeutic and legal settings.